تأثير الأتورفاستاتين على تشتت QT في تخطيط القلب الكهربائي - رضوان, عبد الناصر; بله, حسام; سفاف, جاسم (Latakia University Journal -Medical Sciences Series, 2019)
تمت هذه الدراسة في مشفى الأسد الجامعي باللاذقية خلال عام 2003 على 40 مريضا، تم تقسيمهم إلى ثلاث مجموعات: المجموعة A: مرضى لديهم احتشاء عضلة قلبية، وشملت 20 مريضاً. المجموعة B: مرضى لديهم قصور إكليلي مزمن، وشملت 8 مرضى. المجموعة C: مرضى ليس لديهم أعراض أو علامات سريرية وتخطيطية للقصور الإكليلي، وشملت 12 مريضاً. أجري ECG لجميع المرضى قبل وضعهم على 10ملغ أتورفاستاتين ثم أجري لهم ECG بفواصل شهرين – 6 أشهر – 12 شهر وحُسبَ في كل مرّة تشتت وصلة (QTd) QT ووصلنا إلى النتائج التالية: نقص تشتت QT عند المجموعات الثلاث C-B-A. كان التأثير الأكثر شدة هو عند المجموعة A. لم نلاحظ فرقاً هاماً في نسبة النقص عند المجموعة B وC. ازداد نقص تشتت QT بعد 6 أشهر عنه بعد شهرين من المعالجة بالأتورفاستاتين. لم يلاحظ فرق هام بين QTd بعد 6 أشهر و12 شهر وهذا يعني أن نقص التشتت قد بلغ ذروته بعد 6 أشهر من المعالجة. لوحظ ازدياد QTd من جديد عند أربع مرضى من المجموعة C تم إيقاف الدواء لديهم لمدة شهرين. This study was carried out on 40 patients in AL-ASSAD University hospital in Lattakia during 2003. These Patients were divided into 3 groups: Group A: Patients had myocardial infraction, it included 20 patients. Group B: Patients had coronary insufficiency, it included 8 patients. Group C: Patients with no clinical, electrographic signs of coronary insufficiency or myocardial infraction, it included 12 patients. ECG was carried out to all patients before they took 10 mg of atorvastatine, and after that ECG was carried out in interval of 2 months, 6 months and 12 months. QTd was calculated in every time. We reached the following results: QTd has decreased in the three groups, A, B and C. The greater effect was in group A. We did not notice a significant difference in the decrease rate between group B and C. The decrease of QTd has increased after 6 months of atorvastatine therapy by comparison with QTd of 2 month therapy. No significant difference was noticed between QTd after 6 months and after 12 months, i.e the decreasing of QTd has maximum value after 6 months of therapy. QTd has increased again in 4 patients from group C with whom atorvastatine was stopped for 2 months.